Formation of hydrate particles in the process of gas bubble rising - Nurislamov, O.R.; Lepikhin, S.A.; Galimzyanov, M.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
A theoretical model for the process of methane bubble migration in water under the thermobaric conditions of hydrate formation is proposed. It is shown that two modes of hydrate particle formation are possible depending on the initial depth of bubble rising. A formula relating the hydrate particle porosity on this initial depth is derived. It is taken into account that the hydration shell grows inward along the contact surface between the gas and water penetrating through the pores. The effect of the initial size and depth of bubble formation on the dynamics of the hydrate formation process is analyzed. The dynamics of the hydrate formation process is studied for the following depths of gas sources: 500, 800, 1000, and 1500 m.